CRIMINAL JUSTICE SYSTEM OF CHILDREN: AN OVERVIEW RESTORATIVE JUSTICE CONCEPT IN INDONESIA AND OTHER COUNTRIES - Loura Hardjaloka (Jurnal Dinamika Hukum, 2015)
The pattern of repression in Act No. 3 of 1997 has been changed to a restorative justice through diversion in Act No. 11 of 2012 considering the repressive punishment does not reduce the number of juvenile criminal but increasing. The purpose of this research is to examine the concept of restorative justice in order to see the form of the application of the concept of restorative justice in Indonesia and other countries. The method of this research is judicial normative with secondary data and analyzed based on content analysis. Based on this research, the concept of restorative justice both in Indonesia and other countries is applied through a diversion for the best interest of children (actor), which are implemented in the form of mediation so the children can take their responsibilities for their actions without court trial.Keywords: juvenile justice system, comparative studies, restorative justice, diversion